Identity performance and language policing in Hong Kong's media. (December 2020) - Guo, Quanjiang; Gao, Xuesong (Andy); Shao, Qing; Zhu, Shuran
Abstract: This study reports on our examination of local Chinese residents' identity performance and language policing in Hong Kong's media. In the study, we explored how local Chinese residents police the use of written Chinese in a context where the clash between traditional Chinese characters (associated with Hong Kong) and simplified Chinese characters (associated with mainland China) has been increasingly documented in the media. To examine local Chinese residents' identity performance in language policing incidents, we identified shared social categories from 1311 news articles, comments, and postings online during the years from 2015 to 2019 for analysis. The analysis revealed that antagonism and social categories were presumed and reproduced by those whose participation in language policing incidents against the use of simplified Chinese characters reflects their identity performance. The findings enrich our understanding of how individuals exercise agency in resisting language policies from above, and undertake identity-related performance in language policing to achieve the policy outcomes that they desire to have.